Increasing Risks of Suicide Attempt and Suicidal Drug Overdose After Head Trauma in Patients With Sleep-Disordered Breathing: A Population-Based Study - Harnod, Dorji; Lin, Cheng-Li; Harnod, Tomor; Kao, Chia-Hung (Frontiers in Psychiatry, 2020)
Objective: To determine the risks of suicide attempt (SA) and suicidal drug overdose (SDO) after head trauma in patients with sleep-disordered breathing (SDB) by using the National Health Insurance Research Database of Taiwan. Methods: We analyzed the data of patients aged ≥20 years who were diagnosed with SDB between 2000 and 2012. We further divided them into 2 cohorts [with admission for head injury (SBI) and without (SBN)] and were compared against sex-, age-, comorbidity-, and index-date-matched healthy individuals. The adjusted hazard ratios (aHRs) and 95% confidence intervals of SA and SDO were calculated after adjustment for age, sex, and comorbidities. Results: Approximately 0.30% of patients among the overall 665,725 patients with SDB had SA, with 2013 and 15 patients included in the SBN and SBI cohorts, respectively. Compared with patients with SBN, a significantly higher risk of SA was observed in patients with SBI aged under 50 years, having monthly income less than NTD15,000, living in level 1 and 2 urban areas, and working in offices (aHR = 2.57, 3.59, 3.29, 2.48, and 2.35, respectively). Notably, a SDO incidence of 0.48% was noted in patients with SDB, and the SBI cohort had a 1.80-fold higher risk for SDO when compared with the SBN cohort. Conclusion: The risks of subsequent SA and SDO are proportionally increased by the effects of head trauma with moderating role of SDB, especially in those aged less than 50 years. SDB and head trauma can increase suicide behaviors individually and synergistically.